Code Canvas: Zooming towards Better Development Environments - DeLIne, Robert; Rowan, Kael (Proceedings of the International Conference on Software Engineering (New Ideas and Emerging Results), 2010)
The user interfaces of today’s development environments have a “bento box” design that partitions information into separate areas. This design makes it difficult to stay oriented in the open documents and to synthesize information shown in different areas. Code Canvas takes a new approach by providing an infinite zoomable surface for software develop-ment. A canvas both houses editable forms of all of a project’s documents and allows multiple layers of visualization over those documents. By uniting the content of a project and in-formation about it onto a single surface, Code Canvas is de-signed to leverage spatial memory to keep developers orient-ed and to make it easy to synthesize information.